Roles of OB-Fold Proteins in Replication Stress - Nguyen, Dinh-Duc; Kim, Eugene Y.; Sang, Pau Biak; Chai, Weihang (Frontiers in Cell and Developmental Biology, 2020)
Accurate DNA replication is essential for maintaining genome stability. However, this stability becomes vulnerable when replication fork progression is stalled or slowed − a condition known as replication stress (RS). Prolonged fork stalling can cause DNA damage, leading to genome instabilities. Thus, cells have developed several pathways and a complex set of proteins to overcome the challenge at stalled replication forks. Oligonucleotide/oligosaccharide binding (OB)-fold containing proteins are a group of proteins that play a crucial role in fork protection and fork restart. These proteins bind to single-stranded DNA with high affinity and prevent premature annealing and unwanted nuclease digestion. Among these OB-fold containing proteins, the best studied in eukaryotic cells are replication protein A (RPA) and breast cancer susceptibility protein 2 (BRCA2). Recently, another RPA-like protein complex CTC1-STN1-TEN1 (CST) complex has been found to counter replication perturbation. In this review, we discuss the latest findings on how these OB-fold containing proteins (RPA, BRCA2, CST) cooperate to safeguard DNA replication and maintain genome stability.